(Dis‐)ordering the state: territory in Icelandic statecraft. Issue 1 (27th October 2016) - Clark, Julian; Jones, Alun
Abstract : Foucault and Lefebvre's writings have rekindled interest among geographers in territory–state relations, with recent work conceptualising territory as a state strategy to control space, and on the state as a socio‐natural relation. However, what is lacking is how these debates intersect with post‐human understandings of nature's materialities, and how the resulting 'material territory' mediates state periodisation. Drawing on a case study of Iceland, we address this issue to show how pre‐modern territorialisation shaped state territorialities, and how state periodisation arises from political order imbricating with the materialities of territory. The originality of the work is threefold. First is to show how territory as a material category resists or reinterprets political ordering through longitudinal examination of a single case. Second is to reconceptualise state periodisation as an evolutionary material‐political, as much as socio‐economic, process. Third is to establish empirically the unacknowledged tensions between the state's use of territory to order 'domestic' and 'foreign' affairs. We analyse the implications of a material conception of territory for state periodisation and for wider understandings of contemporary statecraft. The state is revealed as a site of multiple territorialities in space, and territorial multiplicities over time.